The Evolving Regulatory Context for Private Education in Emerging Economies : Discussion Paper and Case Studies - World Bank (Washington, DC : World Bank, 2012)
The approach to regulating private sector education is as unique as the countries in which the institutions are located. Governments are under considerable pressure as they endeavor to meet access to education targets at all levels, from basic to tertiary. Increasingly, governments are recognizing that they are unable to meet these demands without investment from private providers and thus are eager to ensure that providers and investors are of the highest possible quality. Many governments are endeavoring to determine the most appropriate policy framework that will enable the private sector to contribute to national education goals. Regulation of private education is an issue of critical importance for all stakeholders involved: government, providers, investors, parents, and students. How the government frames its regulatory policies will determine the ease, or difficulty, for private providers to enter the market. At their best, regulations can be welcome guidelines to enable quality providers to understand the requirements for working in a given jurisdiction. When regulations are transparent and appropriately applied, they can provide information for parents and students in enabling them to make rational decisions on education choice. This paper briefly examines the international experience concerning the regulation of private education at the school and higher education level.